Microplastics elutriation from sandy sediments: A granulometric approach. Issue 1 (15th June 2016) - Kedzierski, Mikaël; Le Tilly, Véronique; Bourseau, Patrick; Bellegou, Hervé; César, Guy; Sire, Olivier; Bruzaud, Stéphane
Abstract: Although relatively easy to extract in the marine environment, microplastics are very difficult to recover when they are trapped in sediments. The elutriation column is one of the best tools currently available for extracting plastics from sediment, but with a high sand recovery yield. This study aims to address the following questions: ( i ) is it possible to use a sedimentological approach to limit the sand recovery? ( ii ) does the extraction velocity of the sand and plastic particles vary according to density and granulometry? ( iii ) what is the relative recovery efficiency obtained for dense polymer particles mixed with marine sand? Based on a new granulometric classification, different plastic particle-size fractions are defined. Their extraction velocities are experimentally determined on particles of sediment and different plastics (PA, PVC). The particle recovery experiments indicate that it is possible to extract > 90% of dense plastic particles in cases of negligible sand recovery. Highlights: The elutriation column is one of the best tools currently available for extracting plastics. Some methodological approaches allowed to optimize the elutriation process. This methodology has many advantages compared to the conventional methods. The cost, the efficiency and the time are the main advantages of this process.